Health education and prevention amongst the elderly and chronically ill = Edukacja zdrowotna i zapobieganie chorobom wśród osób starszych i przewlekle chorych - Czepczarz, Jarosław; Czepczarz, Agata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to show the importance of evaluation of health education and prevention among the activities of work with the elderly and chronically ill. There are many reasons for these changes, which are influenced by the progress of civilization, as well as the greater possibilities of algorithms for changes in human consciousness. The positive effect of changes can be achieved in gaining knowledge about health and ways of taking care of it. The new era offers us many perspectives on health perception and shows the essence of the importance of preventive measures.
Keywords: health education; health prophylaxis; the elderly; chronically ill; edukacja zdrowotna; profilaktyka zdrowotna; osoby starsze; osoby przewlekle chore